Application of educational technology through three-dimensional images: improving learning in the classroom - Prado Ortega, Mauricio Xavier (2022)
Secondary education institutions currently have the option of using a wide range of techno-pedagogical resources existing in the technology market. The objective of this research study is to improve the learning of secondary school students regarding the incorporation of three-dimensional images in the subjects taught by the teacher using 3D Led-Fan Holographic Display as holographic input. The study was carried out through the research line of educational technology approach in classroom learning environments with a quantitative approach that was based on a case study, using as an analysis instrument the application of surveys to teachers and students of the Kléber Franco School Cross of the city of Machala, carried out before and after the inclusion of holography in the classroom for three months that students from the Pedagogy of Experimental Sciences Pedagogy of UTMACH carried out their pre-professional practices. The results obtained demonstrated an increase in interest and motivation in the students towards the class and greater dynamics of teaching by the teacher. Among the conclusions it is highlighted that LED technology is an option that should be incorporated in the classroom because it is a dynamic resource that awakens attention and improves student learning, which should be disseminated as a teaching alternative for the role that the current teacher plays in empowering himself with the use of ICT.